2008
DOI: 10.1158/1078-0432.ccr-07-4039
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Notch Signaling in a Xenograft Model of Brain Metastasis

Abstract: Purpose: The potential of metastasis can be predicted from clinical features like tumor size, histologic grade, and gene expression patterns. We examined the whole-genome transcriptomic profile of a xenograft model of breast cancer to understand the characteristics of brain metastasis. Experimental Design: Variants of the MDA-MB-435 cell were established from experimental brain metastases. The LvBr2 variant was isolated from lesions in a mouse injected in the left ventricle of the heart, and these cells were u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 19 publications
2
55
0
Order By: Relevance
“…Increased expression of β-catenin by miR-146a was also found in Br4 cells which were isolated through two cycles of injection of LvBr2 cells into the internal carotid artery ( Supplementary Fig. 2D) (Nam et al, 2008). To evaluate whether miR-146a influenced β-catenin expression through the β-catenin 3′UTR, we used a reporter vector that expressed a heterologous GFP mRNA carrying the β-catenin 3′UTR.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Increased expression of β-catenin by miR-146a was also found in Br4 cells which were isolated through two cycles of injection of LvBr2 cells into the internal carotid artery ( Supplementary Fig. 2D) (Nam et al, 2008). To evaluate whether miR-146a influenced β-catenin expression through the β-catenin 3′UTR, we used a reporter vector that expressed a heterologous GFP mRNA carrying the β-catenin 3′UTR.…”
Section: Resultsmentioning
confidence: 93%
“…Brain-trophic metastatic LvBr2 cells showed higher metastatic activity than parent MDA-MB-435 cells MDA-MB-435 cells were reported to form brain metastasis by injection into the left ventricle (LV) of heart or the internal carotid artery (ICA) (Nam et al, 2008;Price et al, 1990). To investigate the role of miRNA in brain metastasis, MDA-MB-435-LvBr cells were isolated from brain metastasis cells after serial LV injection of parent MDA-MB-435 cells (LvBr1 cells were obtained from the first cycle and LvBr2 cells from the second cycle).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the overexpression of HER3 receptor and subsequent activation of MAPK signalling pathway were found to be preferentially activated in the brain metastases of BC patients [36,37]. Preclinical studies demonstrated the stem cell-specific signalling by the Wnt and Notch pathways to be associated with the development of BM [38,39]. Angiogenic factors-the vascular endothelial growth factor (VEGF), angiopoietin-2 and chemokine receptor type 4 (CXCR-4)-have been identified as the specific drivers of BM developmental process [40][41][42][43][44][45].…”
Section: Molecular and Genetic Biomarkers Other Than Hormone And Her2mentioning
confidence: 97%
“…Nam et al reported that the overexpression of Notch-1 and its ligands (DLL-1 and Jag-1) is critical for the survival and proliferation of glioma cells, and the inactivation of Notch signaling can significantly inhibit the migration and invasion of Br4 cells (26). Leong et al observed that Notch-4 activation in human dermal microvascular endothelial cells inhibited endothelial cell sprouting and the vascular endothelial growth factor-induced angiogenesis in the chick chorioallantoic membrane in vivo (27).…”
Section: Discussionmentioning
confidence: 99%